PROFILE OF SANTA CATARINA YOUTH TENNIS PLAYERS WHO ABANDONED THE FEDERATION'S TOURNAMENTS: ITAJAÍ'S REALITY (Fiep Bulletin - online, 2015)
This study identified the profile of young Tennis players who gave up the Federation's Tournament of Santa Catarina State between 1999 and 2003, when they were in the category of 18 years or 21 years old. Twenty ex-Tennis players from Itajaí city took part in the sample. The daa were obtained throught a questionnaire applied to the selected population. A descritive analisys was used to interpret the data. Among the interviewed, 80% (16) are men and 20%(4) are women. They started to practice Tennis between the age of 4 and 14 years; the peak accured with seven years, when most of them startes the practice itself. We noticed that 2 people started the trainning with less than 6 years and 6 people, after 9 years old. The principal reason for them to begin the Tennis practice were: the parents' incentive (with 9 answers), to have fun and entertainment (5), to develop as sportimen (2) and the relative's stimulus (2). We verified that 40% of the children began participate in tournaments between 7 and 10 years old. Related to starting to take part in tournaments, “to compete” and “coach's incentive”: six answers each were got, “entertainment” and “parents' incentive”, two answers. “Choosing the tournament”, the influential person to decide to participate is the players themselves, followes by the coach and their parents. To identify that the parents' and relatives' incentive are pointed as reasons to start practicing Tennis and the coaches' and parents' incentive are pointed as reasons to start competing, we found the one of main the  main factors to motivate the children and youth in the sport is the adults' influence.
Keywords: desistance tournament Tennis.